Endoscopic retrieval of oesophageal foreign body in a dachshund - Pothiappan. P; Giridharan S; Jayanthy. C; Sathishkumar. G; Kavitha. S (Indian Journal of Veterinary Medicine, 2024)
Four-year-old male Dachshund dog was presented to Madras Veterinary College and Teaching Hospital with the history of gradual weight loss and chronic vomiting for more than twenty days. Previously the dog was treated in several places with anti-emetics, proton pump inhibitors, H2 blockers, fluid therapy and antibiotics but there was no improvement. On clinical examination the dog was severely dehydrated, increased skin tenting time and increased capillary refill time. Hematobiochemical assessment revealed mild hypoproteinemia and hypoalbuminemia. Radiographic examination of thorax and abdomen revealed no radio-opaque foreign body in the gastrointestinal tract and ultrasound examination also confirmed the same. Contrast radiographic examination revealed absence of megaesophagus and foreign body in gastrointestinal tract. Hence upper gastrointestinal endoscopy was performed and which revealed presence of plastic thread twine along the esophagus from the level of pharynx to cardia and the foreign body was retrieved using endoscopic forceps. Further the animal was treated with fluid therapy along with other supportive therapy. The dog was shown the clinical improvement after third day.